Perencanaan Pembangunan Pusat Daur Ulang (PDU) Pada CV. Dimensi Ruang Kabupaten Raja Ampat: Planning For The Development Of A Recyling Center (PDU) At CV. Dimensi Ruang Raja Ampat Regency - Karolin, Karolina Batvian; Jauply, Ruben Indra; Effi, Cosmas P.Y.Pao (Universitas Jambi, 2026)
The construction of the Recycling Center (PDU) in Raja Ampat Regency is an important strategic step with the function of being a means to reduce the volume of waste disposed of into the environment, an education center, community empowerment and reuses as a resource of economic value. This research aims to build an initial understanding of the technical documents that form the basis for implementing recycled construction projects. Using the descriptive method, obtained from document studies and planning drawings, the results of this research include the construction location, planning concepts, room types and functions, building construction and material selection.